Phosphatidylinositol 4,5-bisphosphate (PI(4,5)P2)-dependent oligomerization of fibroblast growth factor 2 (FGF2) triggers the formation of a lipidic membrane pore implicated in unconventional secretion - Steringer, Julia P.; Zacherl, Sonja; Andreas, Helena; Laußmann, Mareike; Temmerman, Koen; Contreras, F. Xabier; Lechner, Johannes; Müller, Hans-Michael; García-Sáez, Ana J.; Nickel, Walter (The journal of biological chemistry, 2012)
Fibroblast growth factor 2 (FGF2) is a critical mitogen with a central role in specific steps of tumor-induced angiogenesis. It is known to be secreted by unconventional means bypassing the endoplasmic reticulum/Golgi-dependent secretory pathway. However, the mechanism of FGF2 membrane translocation into the extracellular space has remained elusive. Here, we show that phosphatidylinositol 4,5-bisphosphate-dependent membrane recruitment causes FGF2 to oligomerize, which in turn triggers the formation of a lipidic membrane pore with a putative toroidal structure. This process is strongly up-regulated by tyrosine phosphorylation of FGF2. Our findings explain key requirements of FGF2 secretion from living cells and suggest a novel self-sustained mechanism of protein translocation across membranes with a lipidic membrane pore being a transient translocation intermediate.